Metode Fitoremediasi dalam Pengelolaan Air Tercemar Tembaga (Cu) Berdasarkan Literatur Review - Nasution, Rizki Khoiriah (Universitas Bojonegoro, 2024)
Increased industrialization and urbanization lead to heavy metal pollution of waters, causing serious environmental impacts. Existing microbial technologies to address this problem are often expensive and not always environmentally friendly. Phytoremediation, using plants to remove heavy metals, offers a cheaper and environmentally friendly solution. These methods include phytoextraction, phytostabilization, phytovolatilization, phytofiltration, and phytodegradation. Phytoremediation technology can be applied in-situ or ex-situ, with in-situ methods being more economical. The plants compared in the literature review are Ipomoae aquatica Forks, Salvinia molesta, Pistia stratiotes, Eichhornia crassipes and Sagittaria lancifolia. Based on previous studies, research shows plants such as water hyacinth (Eichhornia crassipes) and spear leaves (Sagittaria lancifolia) are effective in absorbing copper (Cu) from polluted water, making them optimal choices for phytoremediation. This technology provides an efficient and low-cost solution to address heavy metal pollution.